Design of cold-formed high strength steel tubular sections undergoing web crippling. (December 2018) - Li, Hai-Ting; Young, Ben
Abstract: Design of cold-formed high strength steel (HSS) tubular sections undergoing web crippling is examined in this study. Finite element (FE) models were developed and validated against available test results, showing the capability of replicating the experimental web crippling strengths, failure modes and load-web deformation histories. On validation of the FE models, an extensive parametric study comprised of 224 FE analyses was performed. The web crippling provisions in the current North American Specification, Australian/New Zealand Standard and European Code for cold-formed steel structures were assessed. The web crippling strengths obtained from the numerical investigation together with available experimental data from the literature were compared with the nominal strengths derived from the aforementioned specifications. Overall, the comparisons showed that the nominal strengths predicted by the existing codified provisions are either unconservative or overly conservative. Hence, improved design rules are proposed for cold-formed HSS tubular sections undergoing web crippling by means of modified unified equation and Direct Strength Method. The reliability of the modified design rules has been proven through reliability analysis. Highlights: Finite element models of high strength steel tubular sections undergoing web crippling were developed. Parametric study of 224 specimens with web slenderness ratio ranged from 10 to 106 was performed. Existing web crippling design provisions are assessed. New web crippling design rules are proposed.